Efektivitas Pemberian Edukasi Kesehatan tentang PHBS terhadap Perubahan Perilaku Buang Limbah Ikan Masyarakat di Desa Doropayung Juwana - Feby Priscilla Dewi; Feri Catur Yuliani; Ratna (Prodi Keperawatan Purwokerto, 2025)
Background: The fishing industry is a business activity related to the capture, cultivation, processing, storage, distribution, and marketing of fishery products. Only 50% of the fish caught by fishermen is usable for human consumption, compared to the catch intended for human consumption. This results in the accumulation of fish waste. The level of understanding of fishermen plays a crucial role in preventing fish waste disposal. This can be achieved by increasing public awareness of the importance of implementing clean and healthy lifestyles through health promotion education. Purpose: This study aims to determine the effectiveness of providing health education about PHBS in changing the behavior of disposing of fish waste in Doropayung Juwana Village.Method: This study is a quasi-experimental design with pre- and post-tests, but without a control group. The population in this study was local people who process fish in the Doropayung Juwana Village Area. The sampling technique was a total sampling of 45 respondents. Behavior measurement used a questionnaire and an extension of SAP. Data processing used the statistical paired sample t-test. Result: The results prove that it was effective in providing health education about PHBS in changing behavior in disposing of fish waste (p=0.00). Conclusion: Providing health education about PHBS is effective in changing in the behavior of disposing of fish waste.